Підвищення стійкості інтродукованих видів роду Lonicera L. за допомогою хлорхолінхлориду - Bulakh, P.E. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
One year shoots of introduces species of honey-suckle were treated by a method exposition to artificial frost. The results of the test are cited in this paper. The possibility to increase plant resistance by treatment in chlorocholine chloride using different concentrations were considered. The comparative analysis of the data obtained, rhythmics of growth and development of introduced plants is carried out.